Designing social research: a methodological note of the study of state-professions interplay in Bangladesh - Quddus, S. M. Abdul (IIUM Press, 2011)
This paper advances a framework for designing a social research particularly targeting the graduate students who seek assistance in preparing their research proposal, collect data for a scholarly journal article, dissertation, or thesis. However, terms are explained and recommended strategies are advanced in a holistic manner within the context of a developing society like Bangladesh for those needing introductory assistance in the design process of his/her research project and to overcome challenges associated to collect credible data particularly in developing societies.